Analysis of Mathematical Problem-Solving Ability in Terms of Students' Learning Style on Arithmetic Series and Sequence Material - Anggelica Jean; Wike Ellissi (Riemann: Research of Mathematics and Mathematics Education, 2025)
The purpose of this study was to describe the problem solving ability of each type of learning style of students in class XI IPA SMA Negeri 2 Ngabang in solving math problems on the material of arithmetic rows and series. The type of research used is descriptive qualitative research. Data collection techniques using questionnaires, tests and interviews. The research subjects consisted of 6 students of class XI IPA SMA Negeri 2 Ngabang. Subject selection based on purposive sampling technique. Data analysis techniques used in this study are data reduction, data presentation and conclusion drawing. The results of this study indicate 1) students with a visual learning style are able to understand the problem well, able to make a solution plan, able to carry out the plan and can recheck the answer results by looking back at the problem and checking the calculations, 2) students with an auditory learning style are able to understand the problem well, have not been able to make a solution plan, not yet able to implement the plan and at the stage of checking back auditory students can recheck the results of the answer by looking back at the problem and checking the calculations, 3) students with kinesthetic learning styles are able to understand the problem well, are able to make a solution plan, have not been able to at the stage of implementing the plan and at the stage of checking back kinesthetic students can recheck the results of the answer by looking back at the problem and checking the calculations. This research can help students to know the problem solving process in solving math problems.